GRADUATES’ PROMOTION ON LABOR MARKET AND TRACKING THEIR CAREER: THE EXPERIENCE OF NOVOSIBIRSK STATE UNIVERSITY - S. S. Donetskaya; S. V. Dovgal (Высшее образование в России)
The article highlights the experience of Novosibirsk State University in preparation of specialists demanded by the labor market and in organization of student support in the process of employment. Special attention is paid to the organization of graduates’ career monitoring. The potential employers of university graduates are necessarily involved in the educational process and the development of the new academic disciplines and programs. Assistance in the employment process includes organization of meetings with employers and business coaches as well as representatives of headhunters agencies. The monitoring of the graduates’ employability is carried out to identify their actual level of employment and the relevance of knowledge gained. It allows to estimate successfulness of the educational process and the relevance of education areas. The survey is organized on an annual basis for the last-year graduates, and then it is repeated every 5-10 years. The article presents the results of two surveys of the graduates (2006 and 2016). Graduates of the 2010-2016 were interviewed in 2016, graduates of 1991-2004 – in 2006. Graduates of the 2010-2016 were interviewed in 2016, 1991-2004 – in 2006. The results showed that the level of graduates’ job placement within their specialty obtained on the departments focused on scientific activity has not changed during the last 25 years. Approximately 90% of graduates were working within their specialty during the first year after graduation from the university. This value reduces slightly over time. The same can be said about the graduates of the departments of information technologies and law. At the same time, the percentage of the graduates of economic specialties involved in business have declined by half.